The triangulation between Arctic birds, Arctic foxes and Arctic lemmings - Angerbjörn, Anders; Tannerfeldt, Magnus; Svensson, Sören (Frontiers in Ecology and Evolution, 2026)
Many studies have suggested that Arctic predators preying on lemmings, especially the Arctic fox, take advantage of the high prey densities during peak years, but have to switch to alternative prey during years of low lemming density, thereby forcing other prey species into the basic lemming cycle. Data on the number of breeding geese and waders in Arctic areas show three-year cycles, supporting this hypothesis. There are two alternative explanations for such a prey switch. The switch to the alternative prey could be due to a functional prey response, which assumes that the proportion of birds in fox diet should be related to lemming population phase due to a type III functional response between foxes and lemmings. The numerical switch explanation on the other hand, assumes that bird numbers should be related to lemming population phase because of a time lag in the numerical response between foxes and lemmings. With data on the diet and population numbers of Arctic foxes, Arctic lemmings and Arctic birds from eight different sites in northern Siberia, we tested these hypotheses. The use of birds in fox diet was not related to lemming population phase. Instead, we found a time lag in numerical response to lemmings, thus supporting the numerical switch explanation for the alternative prey hypothesis.